Morphological characterization of Streptocephalus sirindhornae (Branchiopoda: Anostraca) from South East Asia: First record of the Streptocephalidae from China - Shu, Shusen; Maeda-Martinez, Alejandro M.; Rogers, D. Christopher; Yang, Junxing; Chen, Xiaoyong (Zootaxa, 2015)
During a zooplankton study in southern China, Streptocephalus specimens were collected from ephemeral ponds located in the Yunnan Province and the Guangxi Zhuang Autonomous Region. We determined that the specimens from both locations are Streptocephalus sirindhornae Sanoamuang, Murugan, Weekers, and Dumont, 2000. This documents are the first records of Streptocephalidae in China, which represent its northern and easternmost distributional edge in East Asia. All specimens are deposited in Kunming Natural History Museum of Zoology, Kunming Institute of Zoology (KIZ), Chinese Academy of Sciences (CAS). The morphological terminology follows Rogers and Padhye (2014) and the material is compared with the original description (Sanoamuang et al., 2000).